Pola Sidik Jari pada Daerah Kecamatan Bandar Khalipah - Efrilia, Celline; Armiati, Rika; Anggraini, Lisa; Ayundari, Sella; Dwijayanti, Ummi Nur Afinni (Ikatan Dai Indonesia, 2023)
The fingerprint pattern is one of the genetically regulated phenotypes and is formed in the early embryo, which is approximately 18 weeks of gestation. The shape and characteristics will remain and will not be affected by the environment from birth until the person dies. In the fingerprint pattern there are three characteristics, namely the type of fingerprint pattern, the number of triradius and total tendrils. The fingerprint patterns are grouped into wholr type, ulna loop, radial loop. and arch. In this research, it was carried out using qualitative research methods. The object of research was direct observation of broadness, so that this research obtained not so many numbers, but more descriptive. The data used in this study were primary data obtained directly from the field. Which aims to determine the fingerprint patterns of individuals in the Bandar Khalippah sub-district, and also identify fingerprint patterns, and count the number of tendrils in the human population in the Banda Khalippah sub-district.